Alternance lexicale : structures, situations et domaines d’emploi - Moufoutaou Adjeran (Multilinguales)
The practice of French and / or English allows to appreciate lexical-alternations hitherto confused, neology. From the distinction between neology and lexical alternation, it emerges that the neology does not imply a particular situation in the linguistic environment. The analysis of hybrids facilitates the reading of their structures, situations and fields of use.